Imaging Findings and Misdiagnosis of Bronchogenic Cysts: A Study of 83 Cases - Xiaoyu Gu; Li Zhu; Yingming Li; Bo Yin; Zhongqiu Wang (Journal of the Belgian Society of Radiology, 2023)
Objective: We characterize computed tomography (CT) and magnetic resonance imaging (MRI) features of bronchogenic cysts (BCs) and analyze misdiagnosis. Methods: The retrospective study consisted of 83 patients with BCs. CT and MRI images were assessed for mass location, maximum diameter, density, calcification, signal intensity, and enhancement pattern. Eighty-three patients underwent plain CT in which 53 underwent enhanced CT. Thirteen patients received both plain and enhanced MR, and only one received just a plain MR. Results: Eighty-three masses were all solitary, with 71 having a roundish morphology, and twelve having a lobulated or irregular morphology. Sixty-six masses are mediastinal type, four are intrapulmonary type, and 13 are ectopic type. Calcification occurred in 14 lesions. On plain CT, 13 lesions displayed water-like attenuation (–20–20 Hu), and 70 showed soft-tissue attenuation (≥21 Hu). On T1WI, eight masses were hyperintense, three were isointense, and three were hypointense. Fourteen masses were hyperintense on T2WI and (Apparent Diffusion Coefficient) ADC sequence. On (Diffusion Weighted Imaging) DWI, six masses were hypointense and eight were hyperintense. Enhanced T1WI showed seven cases were unenhanced, while six were marginally enhanced. Twenty cases were misdiagnosed as thymomas, eleven as neurogenic tumors, six as lymphangiomas, and two as lung cancer. Five cases were misdiagnosed as other diseases. Patients with BCs underwent MR (42.9%) had a lower rate of misdiagnosis than those who underwent CT alone (53.0%). Conclusion: The imaging findings of BCs in the chest are generally consistent. Misdiagnosis occurs frequently when CT attenuation values exceed 20 Hu. Diagnostic accuracy of BCs tends to improve with preoperative MR examination.